DIAGNÓSTICO E ANÁLISE COMPARATIVA DO PROCESSO DAS ETAPAS INICIAIS DE PROJETO ENTRE EMPRESAS ATUANTES NA CONSTRUÇÃO CIVIL - Michaud, Carolina Rodrigues; Iarozinski Neto, Alfredo; Faganello, Adriana; Matoski, Adalberto (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The systematization of the project process can provide improvements in the final results of the project. The objective of this exploratory study was to identify and highlight the main factors that may influence the development of the project. Based on this research was developed a questionnaire, applied among several companies designers in the area of civil construction. The answers of the questionnaire were statistically analyzed using descriptive and inferential statistics techniques. For the analysis, the participating companies were divided into four groups, architectural design firms (PA), engineering design companies (PE), construction companies and incorporators (CI) and "others" (O), with the objective of analyzing separately how each of the sectors behaves in relation to the design process. The descriptive analysis of the answers of the questionnaire allowed to characterize the companies in relation to the organizational characteristics, project practices and management processes. The inferential analysis made it possible to differentiate the participating companies, highlighting the factors that most distinguish the groups.